Internal branding as a tool for integrated organisational alignment - Julia Scheffer; Andrea Crystal (Communicare)
Within an evolving business environment, it is central to the continuing success of organisations that internal communication be taken into consideration in the quest to increase organisational competitive advantage. This paper explores the importance of an alignment existing between internal organisational values and the external organisational image. As such, to guarantee the promotion of employee satisfaction through an internal organisational alignment strategy, improvement should be made to internal communication strategies. As it implemented internal branding initiatives so as to align internal stakeholders with the core organisational values and its external corporate brand image, Absa Bank is the chosen sample. Through qualitative research, the participants concur that the aim of the internal branding initiative is to improve the quality of service rendered, to retain external customers, and to impact positively on the bank’s profitability. Based on the research, the data analysis reveals that a key contribution is the conceptualisation of the term ‘integrated organisational communication’.